2015
DOI: 10.1007/s11676-015-0184-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessing bacterial communities in the rhizosphere of 8-year-old genetically modified poplar (Populus spp.)

Abstract: Microbe communities in rhizosphere ecosystems are important for plant health but there is limited knowledge of them in the rhizospheres of genetically modified (GM) plants, especial for tree species. We used the amplitude sequencing method to analyze the V4 regions of the 16S rRNA gene to identify changes in bacterial diversity and community structure in two GM lines (D520 and D521), one non-genetically modified (non-GM) line and in uncultivated soil. After chimera filtering, 468.133 sequences in the domain Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…These results indicated that expression of the AhDREB1 gene in Populus does not affect the number of culturable microorganisms present. Similar results were also shown by Zhu et al [35]; in their study, there was no or very limited impact of an eight-year-old transgenic poplar on the bacterial communities in the rhizosphere. However, more than 90% of microorganisms are not culturable [36].…”
Section: Discussionsupporting
confidence: 90%
“…These results indicated that expression of the AhDREB1 gene in Populus does not affect the number of culturable microorganisms present. Similar results were also shown by Zhu et al [35]; in their study, there was no or very limited impact of an eight-year-old transgenic poplar on the bacterial communities in the rhizosphere. However, more than 90% of microorganisms are not culturable [36].…”
Section: Discussionsupporting
confidence: 90%
“…Transgenic tobacco also had altered rhizosphere/rhizoplane microbial communities; however, these effects were temporary, and the diversity of the community was restored to the original level after one cycle of plant cultivation (Andreote et al, 2008). Previous research in our laboratory found no significant differences in bacterial communities between rhizosphere soils of 8-year-old GM and non-GM poplars ( Populus × euramericana ‘ Guariento ’) (Zhu et al, 2016). Our transgenic poplar is different from most transgenic plants in that the exogenous gene, the JERF transcription factor, does not contain the Bt gene, and does not release the BT protein into the plant body and surrounding soil.…”
Section: Discussionmentioning
confidence: 53%
“…However, to date, studies on the effects of transgenic plants on the rhizosphere and endogenous microorganisms have mainly focused on annual crops or herbaceous plants, while there are few reports on trees with long growth cycles. Previous research in our laboratory found no significant differences in bacterial communities between rhizosphere soils of 8-year-old genetically modified (GM) and non-GM poplar ( Populus × euramericana ‘Guariento’) (Zhu et al, 2016).…”
Section: Introductionmentioning
confidence: 67%
“…In forestry, transgenic genetic poplar, such as insect resistant transgenic poplar, has been approved and become possibility of deployment ( Jing et al, 2004 ; Guifeng et al, 2006 ; Guifeng et al, 2006 ; Zhou et al, 2018 ). More transgenic poplars are still in the stage of trial and environmental risk assessment ( Lu et al, 2014 ; Zhu et al, 2016 ; Hu et al, 2017 ). Five years of field monitoring of the Bt transgenic 741 poplar showed that the introduction of the Bt gene has neither affected the stability of arthropod communities nor the rhizosphere soil physicochemical properties and microbial community structure ( Zuo et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%